Coordination and policy traps - George-Marios Angeletos; Christian Hellwig; Alessandro Pavan (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2005)
This paper examines the ability of a policy maker to control equilibrium outcomes in a global coordination game; applications include currency attacks, bank runs, and debt crises. A unique equilibrium is known to survive when the policy is exogenously fixed. We show that, by conveying information, endogenous policy re-introduces multiple equilibria. Multiplicity obtains even in environments where the policy is observed with idiosyncratic noise. It is sustained by the agents coordinating on different interpretations of, and different reactions to, the same policy choices. The policy maker is thus trapped into a position where both the optimal policy and the coordination outcome are dictated by self-fulfilling market expectations.
Keywords: C7; D8; E5; E6; F3; 330; global games; complementarities; signaling; self-fulfilling expectations; multiple equilibria; currency crises; regime change; Devisenspekulation; Spieltheorie; Wechselkurspolitik; Koordination; Gleichgewicht; Theorie